Hubungan Kecemasan Pasien Diabetes Melitus Terpapar COVID-19 Dengan Kunjungan Ke Poli Penyakit Dalam: The Relationship Between Anxiety of Diabetes Mellitus Patients Exposed to COVID-19 With Visits to Internal Medicine Polyclinics - PUSPITA, PIPIT (Dohara POAJ, 2022)
Introduction: The condition of the current COVID-19 pandemic has an impact on everyone's mental health including the anxiety of Diabetic Mellitus patients in making visits to the Internal Medicine Poly for fear of exposure to covid-19 which can worsen the disease. Purpose: To find out the anxiety relationship of Diabetic Mellitus patients exposed to COVID-19 with a visit to the Internal Medicine Poly. Method: The research used is a descriptive correlation with cross-sectional approaches. The population in this study was 130 people. The samples were taken with a simple random sampling technique in 57 patients with diabetes mellitus. The data was taken using questionnaires. Result: Data analysis uses univariate and bivariate data using the Chi-Square test. The results of this study showed that there was a relationship between the anxiety of Diabetic Mellitus patients exposed to COVID-19 with visits to the Internal Medicine Poly (p-value = 0.001). Conclusion: There is a relationship between the anxiety of Diabetic Mellitus patients exposed to COVID-19 and visits to the Internal Medicine Poly. Of the 57 patients with Diabetes Mellitus, there were 41 respondents who were severely anxious, of which 33 (57.9%) respondents did not want to visit the internal medicine poly. In the future, it is expected that the hospital can improve the understanding of diabetes mellitus patients to make a repeat visit to the Internal Medicine Poly by complying with health protocols so as not to be exposed to COVID-19.